ANALISIS PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN YANG DIMEDIASI OLEH CITRA MEREK SMARTPHONE OPPO - Andika Bagus Saktiawan; Wiyadi (POLITEKNIK LP3I JAKARTA, 2024)
This study aims to analyze the effect of product quality, price, and promotion on purchasing decisions mediated by brand image. This study uses a survey of 110 students of the Faculty of Economics and Business, Muhammadiyah University of Surakarta who have purchased Oppo smartphones as research objects. The findings of the study indicate that product quality, price, and promotion significantly affect brand image. However, the effect of price on brand image is not significant. In addition, this study reveals that brand image significantly mediates the effect of product quality and promotion on purchasing decisions. These findings emphasize the importance of having a positive brand image in influencing consumer purchasing decisions. The conclusion of this study is that companies should prioritize building a positive brand image and providing high-quality products at attractive prices. By promoting products effectively, companies can influence consumer perceptions and ultimately increase sales. This study provides valuable insights for companies in designing more effective marketing strategies and optimizing factors that influence consumer purchasing decisions.